A biochronologic tie-point for the base of the tortonian stage in european terrestrial settings: Magnetostratigraphy of the topmost upper freshwater molasse sediments of the north alpine foreland basin in bavaria (Germany) - Kirscher, Uwe; Prieto, J.; Bachtadse, V.; Abdul Aziz, H.; Doppler, G.; Hagmaier, M.; Böhme, M. (2016)
Chronostratigraphic correlation and dating of terrestrial, especially mammal bearing, sediments of the European Neogene are still problematic and highly debated. In particular, absolute ages for important vertebrate assemblages are often not available making correlation during the continental Miocene across Europe so ambiguous. Here we present a detailed magnetostratigraphic study on a paleontological key section of the Middle to Late Miocene transition in the North Alpine Foreland Basin (NAFB) in Bavaria (Hammerschmiede) and a neighboring drill core, which has a total length of 150.4 m and includes, stratigraphically, the fossil site. We identify three complete normal polarity intervals, which have been correlated based on biochronologic constraints to chrons C5An.1n, C5r.2n and C5r.2r-1n. At least two major hiatuses probably occurred within the interjacent reversed chrons, for which geological indications are present and might be relatable to isochronic features in the Vienna basin. Inferred upper limits of the accumulation rate vary between 10 and 30 cm/kyr. This correlation determines the age of the Hammerschmiede vertebrate level HAM 5 to be about 11.62 Ma, making it an ideal biochronologic tie-point for the base of the Tortonian and Pannonian stages in terrestrial settings. Additionally, we date the youngest freshwater molasse lithostratigraphic unit of the Bavarian part of the NAFB, the Obere Serie, to between 13.8 and 11.1 Ma. Following our correlation, the lack of hipparion horses in the Bavarian part of the NAFB has stratigraphic rather than ecologic reasons and the 'Hipparion datum' seems to be a single bio-event at 11.1 Ma in Western Eurasia.